Graftable condensed ring material, colored light conversion adhesive film and photovoltaic module
Coupling color-light conversion materials with adhesive films through graft cross-linking technology solves the problem of uneven traditional adhesive films, and improves the service life of the adhesive film and the efficiency of photovoltaic modules.
Patent Information
- Application Number
- CN202411394776.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-02-18
AI Technical Summary
Traditional films doped with chromolight converters have the problem of film unevenness, which affects its service life and the efficiency of photovoltaic modules.
Through graft cross-linking technology, the color light conversion material of small molecules is coupled to the adhesive film through free radical initiation and the base film to form a more uniform film.
It improves the service life of the color-light conversion film and the efficiency of photovoltaic modules, and extends the service life of photovoltaic equipment.
Smart Images

Figure CN119463129A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic materials, and in particular to a graftable condensed ring material, a color-conversion adhesive film and a photovoltaic module, and in particular to a graftable condensed ring material, a color-conversion adhesive film with high migration resistance and strong aggregation resistance made therefrom, and a photovoltaic module using the adhesive film. Background Art
[0002] Solar cell systems are one of the most promising systems due to their low environmental impact. Although solar cell systems have long been very reliable under field conditions with low degradation and failure rates, they are still susceptible to ultraviolet light in sunlight. The current effective solutions are to use cut-off films to filter ultraviolet light, but this method will lose ultraviolet energy; the second is to use films doped with color light conversion luminescent materials to achieve red shift of the wavelength of ultraviolet photons that are harmful to the cell, and transform the band to the visible light region that can be used by solar cells, thereby improving the efficiency of solar cells. However, traditional films doped with color light conversion agents have the problem of film inhomogeneity, which seriously affects the use of the film.
[0003] Therefore, in order to solve the above technical problems, it is urgent to develop a color conversion material that can be stably dispersed in the photovoltaic film. Summary of the invention
[0004] Due to the above-mentioned defects in the prior art, the present invention provides a color conversion material that can be stably dispersed in a photovoltaic adhesive film. Specifically, the problem of uneven film in the prior art adhesive film doped with a color conversion agent is solved by grafting and cross-linking technology. The small molecule color conversion material is grafted into the adhesive film by a cross-linking method, and the small molecule and the adhesive film are directly coupled by free radical initiation and base film formation CC to form a more uniform film, thereby improving the service life of the color conversion adhesive film.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A graftable condensed ring material includes a compound having a structure shown in (I) or (II):
[0007]
[0008] Wherein, R1 and R2 are selected from H, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted heteroalkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, substituted or unsubstituted amino, substituted or unsubstituted amide, substituted or unsubstituted cycloimido, substituted or unsubstituted alkoxy, substituted or unsubstituted carboxyl, substituted or unsubstituted ester, substituted or unsubstituted carbonyl, and R1 and R2 are not H at the same time; the substituted substituents include C1~C20 Hydroxyl, C1~C 20 Ester group, C1~C 20 Carboxyl, C1~C 20 Amino, C1~C 20 Thiol, C1~C 20 Amide group, C1~C 20 Carbonyl, C1~C 20 Alkoxy, C1~C 20 Aryl, C4~C 20 Heteroaryl, C1~C 20 Alkyl, C1~C 20 Heteroalkyl, C1~C 20 Alkenyl and C1~C 20 Any of the imino groups;
[0009] The L is taken from C1~C 20 Alkylene, C1~C 20 Ether group, C1~C 20 Ester group, C1~C 20 Imino, C1~C 20 Imido, C1~C 20 Carbonyl, C1~C 20 Arylene, C1~C 20 Alkenylene, C1~C 20 Any of alkynylene;
[0010] The Ar1, Ar2 and Ar3 are independently selected from null, substituted alkylene, optionally substituted alkenylene, optionally substituted arylene, optionally substituted heteroarylene, ketone, ester and m=0-10000, Ar is an optionally substituted aryl or an optionally substituted heteroaryl; R3 is selected from H, alkyl, alkenyl, aryl, heteroaryl, aralkyl and alkaryl;
[0011] n = 1 to 10000;
[0012] x+y=1.
[0013] The graftable polycyclic material of the present invention has a vinyl terminal and can be grafted with various resins (such as POE, EVA) through a simple reaction (through free radical initiation and resin-based film coupling to form CC connection), thereby cross-linking to the resin, fundamentally avoiding the migration problem between small molecules, and the uniformity of the overall film is good, thereby improving the service life of the color light conversion film, that is, the graftable polycyclic material of the present invention can be cross-linked with most films to form a stable color light conversion film, thereby having a longer service life, further extending the service life of photovoltaic equipment, and having good application prospects.
[0014] As the preferred technical solution:
[0015] In the graftable fused ring material as described above, the substituents in the optionally substituted aryl group and the optionally substituted heteroaryl group are each independently selected from one or more of the following groups: 20 Alkyl, C1-C 20 Alkenyl, C1-C 20 Alkynyl, C3-C7 cycloalkyl, geminal cycloalkyl, C1-C 20 Heteroalkyl, C3-C 20 heterocycloalkyl, aryl, aralkyl, heteroaryl, halo, cyano, hydroxy, optionally substituted cyclic imido, amino, imido, acylamino, C1-C 20 Alkoxy, aryloxy, acyloxy, mercapto, halogenated (C1-C 20 ) alkyl, C1-C 20 Alkylthio, arylthio, mono- and di-(C1-C 20 ) alkylamino, quaternary ammonium salt, amino (C1-C 20 ) alkoxy, hydroxyl (C1-C 20 ) alkylamino, amino (C1-C 20 ) alkylthio, cyanoamino, nitro, carbamoyl, oxy, carbonyl, carboxyl, glycolyl, glycyl, hydrazine, amidino, sulfonamide, sulfonyl, sulfinyl, thiocarbonyl, thiocarboxyl, sulfonamide, ester, C-amide, N-amide, N-carbamate, O-carbamate, urea, and combinations thereof.
[0016] The graftable fused ring material as described above, wherein R1 and R2 are independently selected from H, substituted or unsubstituted C1-C 20 Alkyl, substituted or unsubstituted C1~C 20 Any of alkenyl.
[0017] The graftable fused ring material as described above comprises any one or a combination of at least two of the following compounds:
[0018]
[0019] The present invention also provides a color light conversion adhesive film, wherein the raw materials for preparing the color light conversion adhesive film include the graftable condensed ring material as described above.
[0020] As the preferred technical solution:
[0021] The color light conversion adhesive film as described above, the preparation raw materials also include the following components: resin, cross-linking agent, modified silane, acrylate, light stabilizer and anti-stabilizer.
[0022] The present invention does not specifically limit the preparation method of the color conversion adhesive film, which can be prepared according to a conventional method. For example, taking the preparation method of the color conversion adhesive film-grafted POE adhesive film as an example, it includes the following steps:
[0023] The POE particles, a graftable color light conversion agent, namely a graftable condensed ring material, a crosslinking agent, a modified silane, an acrylate, a light stabilizer and an antioxidant are mixed, and the mixture is plasticized by a screw and co-extruded and casted by a die to obtain a grafted POE film.
[0024] The color light conversion adhesive film as described above, wherein the raw materials for preparation include the following components in parts by weight:
[0025]
[0026] By controlling the content of each component within the above range, the prepared grafted adhesive film can have better comprehensive properties, for example, higher anti-migration and anti-precipitation properties and bonding strength.
[0027] Preferably, in parts by weight, the amount of resin can be 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts or 95 parts, etc.; the amount of graftable condensed ring material can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts, etc.
[0028] A color light conversion adhesive film as described above, wherein the resin includes any one or a combination of at least two of polyvinyl acetate, polyethylene-octene copolymer, polyvinyl butyral, hot-melt polyolefin particles or thermoplastic polyurethane;
[0029] The cross-linking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, triallyl isocyanurate, triallyl cyanurate, diisopropylbenzene peroxide, benzoyl peroxide, di-tert-butyl peroxide or diisopropylbenzene hydroperoxide, or a combination of at least two thereof;
[0030] The modified silane includes any one or a combination of at least two of isocyanatepropyl trioxyethyl silane, vinyl triacetoxy silane, methacryloxypropyl trimethoxy silane derivatives, alkylamino silane oligomers, alkylvinyl silane oligomers, epoxy silane oligomers, amino silane oligomers, small molecule polysiloxanes, mercapto silane derivatives or hybrid functional silanes;
[0031] The acrylate includes any one of ethoxylated trimethylolpropane triacrylate, propoxylated trimethylol triacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, polyethylene glycol diacrylate, tricyclohexane dimethanol diacrylate or ditrimethylolpropane tetraacrylate, or a combination of at least two thereof;
[0032] The light stabilizer includes any one of succinic acid, a polymer of 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, bis-2,2,6,6-tetramethylpiperidinol sebacate or a hindered amine light stabilizer, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(2,4-di-tert-butylphenyl) phosphite or 2,2,6,6-tetramethyl-4-piperidinyl ester or a combination of at least two thereof;
[0033] The antioxidant includes any one of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or tris[2,4-di-tert-butylphenyl]phosphite or a combination of at least two thereof.
[0034] In addition, the present invention also provides a photovoltaic module, that is, the use of a color conversion adhesive film made of a grafted condensed ring material in a photovoltaic module, wherein the photovoltaic module comprises the color conversion adhesive film and a battery as described above.
[0035] As the preferred technical solution:
[0036] The photovoltaic module as described above, wherein the cell comprises any one or a combination of at least two of an indium gallium arsenide solar cell, an organic solar cell, a perovskite solar cell, a cadmium sulfide / cadmium telluride solar cell, an amorphous silicon solar cell, a microcrystalline silicon solar cell, and a crystalline silicon solar cell.
[0037] The above technical solution is only a feasible technical solution of the present invention, and the protection scope of the present invention is not limited thereto. Those skilled in the art can reasonably adjust the specific design according to actual needs.
[0038] The above invention has the following advantages or beneficial effects:
[0039] (1) The graftable condensed ring material of the present invention has a vinyl terminal and can be grafted with various resins (such as POE, EVA) through a simple reaction (through free radical initiation and resin base film coupling to form CC connection), thereby cross-linking to the resin, fundamentally avoiding the migration problem between small molecules, and the overall film has good uniformity, thereby improving the service life of the color light conversion adhesive film;
[0040] (2) Compared with the traditional color-conversion adhesive film, the color-conversion adhesive film made of the grafted polycyclic material of the present invention can be more stably present in the adhesive film in which the color-conversion agent connected to the adhesive film by chemical bonds, thereby avoiding the aggregation and precipitation of the conversion agent, and can significantly improve the service life of the adhesive film, that is, extend the service life of the photovoltaic module, thereby improving the economy of the photovoltaic module and having good application prospects. DETAILED DESCRIPTION
[0041] The present invention will be further described below in conjunction with specific embodiments, but they are not intended to limit the present invention.
[0042] Example 1
[0043] A graftable condensed ring material Xa, the specific structural formula is
[0044]
[0045] The preparation method comprises the following steps:
[0046] (1) In a N2 atmosphere, sodium tert-butoxide (200 g) was slowly added to a mixed solution of 2,7-dibromofluorene (324 g), 8-bromo-1-octene (400 g) and anhydrous tetrahydrofuran (500 ml). After the addition was complete, the reaction was continued for 6 hours. After the reaction was completed, cold water and dichloromethane were added for extraction. The organic layer was taken and dried over anhydrous sodium sulfate, filtered, concentrated under reduced pressure, and the concentrate was recrystallized from methanol to obtain 9,9-di(7-octenyl)-2,7-dibromofluorene (yield 95%).
[0047] (2) The intermediate product (54.6 g) obtained in step (1), phenylboric acid (40 g), PbCl2(PPh3)2 (50 mg) and potassium carbonate (30 g) were added to a reactor and deoxygenated with nitrogen. Then, N,N-dimethylformamide (DMF, 45 mL) was injected into the reaction vessel under a nitrogen atmosphere, and deionized water (200 mL) previously deoxygenated by nitrogen bubbling was added to the reaction vessel. The mixture was stirred at 90° C. for 4 h. After the reaction was completed, deionized water (2 L) was added to obtain a precipitate. The precipitate was dissolved in ethyl acetate (500 mL), and n-hexane (150 mL) was added to obtain a black precipitate. After removing the black precipitate, the organic solution was concentrated by vacuum distillation, and the concentrate was recrystallized with isopropyl alcohol (IPA) to obtain a graftable condensed ring material, i.e., a color light conversion agent Xa (yield 78.1%).
[0048] Example 2
[0049] A graftable condensed ring material Xb, the specific structural formula is
[0050]
[0051] The preparation method is basically the same as that of Example 1, except that step (2) is as follows: the intermediate product (54.6 g) obtained in step (1) of Example 1, 4-butoxyphenylboronic acid (40 g), PbCl2(PPh3)2 (50 mg) and potassium carbonate (30 g) are added to a reactor and deoxygenated with nitrogen; then N,N-dimethylformamide (DMF, 45 mL) is injected into the reaction vessel under a nitrogen atmosphere, and the mixture is deoxygenated with nitrogen bubbling. Deionized water (200 mL) was added to the reaction vessel, and the reaction was stirred at 90°C for 4 hours. After the reaction was completed, deionized water (2 L) was added to obtain a precipitate; the precipitate was dissolved in ethyl acetate (500 mL), and n-hexane (150 mL) was added to precipitate a black precipitate. After removing the black precipitate, the organic solution was concentrated by vacuum distillation, and the concentrate was recrystallized with isopropyl alcohol (IPA) to obtain a grafted condensed ring material, i.e., a color light converter Xb (yield 73.6%).
[0052] Example 3
[0053] A graftable condensed ring material Xc, the specific structural formula is
[0054]
[0055] The preparation method comprises the following steps:
[0056] (1) In a N2 atmosphere, sodium tert-butoxide (20 g) was slowly added to a mixed solution of 2,7-dibromofluorene (32.4 g), 2-acrylic acid-4-bromobutyl ester (40 g) and anhydrous tetrahydrofuran (100 ml). After the addition was complete, the reaction was continued for 6 hours. After the reaction was completed, cold water and dichloromethane were added for extraction. The organic layer was taken and dried over anhydrous sodium sulfate, filtered, concentrated under reduced pressure, and separated by silica gel column to obtain 9,9-di(2-acrylic acid-4-butyl)-2,7-dibromofluorene (yield 35%);
[0057] (2) The intermediate product (5.46 g) obtained in step (1), phenyl borate (4 g), PbCl2(PPh3)2 (50 mg) and potassium carbonate (3 g) were added to a reactor and deoxygenated with nitrogen; then, N,N-dimethylformamide (DMF, 40 mL) was injected into the reaction vessel under a nitrogen atmosphere, and deionized water (10 mL) previously deoxygenated by nitrogen bubbling was added to the reaction vessel, and the reaction was stirred at 90° C. for 4 h. After the reaction was completed, deionized water (200 ml) was added to obtain a precipitate; the precipitate was dissolved in ethyl acetate (200 mL) and extracted, and after concentration, it was separated and purified by a silica gel column to obtain a graftable condensed ring material, i.e., a color light conversion agent Xc (yield 52.1%).
[0058] Example 4
[0059] A graftable condensed ring material Xe, the specific structural formula is
[0060]
[0061] The preparation method comprises the following steps:
[0062] The first step product (0.544 g) of Example 1, 9,9-dioctyl-2,7-dibromofluorene (4.91 g) and dimethyltin-thiophene (4.65 g) were placed in a reactor and deoxygenated by nitrogen; then 100 ml of toluene was injected into the reactor under nitrogen atmosphere and stirred at 110° C. for 6 hours. After the reaction was completed, 200 ml of methanol was added to obtain a precipitate; the precipitate was subjected to Soxhlet extraction to obtain a graftable condensed ring material, i.e., a color light conversion agent Xe. Mn: 18.6; PDI: 2.4.
[0063] Application Example 1
[0064] A color light conversion film, the raw materials and dosage of which are shown in Table 1:
[0065] Table 1
[0066]
[0067]
[0068] The preparation method is as follows: POE particles, graftable polycyclic material Xa, crosslinking agent, modified silane, acrylate, light stabilizer and antioxidant are mixed in a formulated amount, plasticized by a screw at 105°C, and co-extruded by a die to obtain a color light conversion adhesive film, namely, a color light conversion POE film.
[0069] Application Example 2
[0070] A color light conversion adhesive film, the raw materials and dosage of which are shown in Table 2:
[0071] Table 2
[0072]
[0073] The preparation method is the same as that of Application Example 1.
[0074] Application Example 3
[0075] A color light conversion film, the raw materials and dosage of which are shown in Table 3:
[0076] Table 3
[0077]
[0078] The preparation method is the same as that of Application Example 1.
[0079] Comparative Example
[0080] The preparation scheme, added medium and auxiliary agent of this comparative example are the same as those of Application Example 1, except that the graftable polycyclic material Xa is replaced with a commercial ultraviolet absorber UV326, and finally a conventional POE film is obtained after cast extrusion.
[0081] The performance comparison test of the color light conversion POE film prepared in Application Examples 1 to 3 and the conventional POE film prepared in the comparative example was conducted. The specific test detected the maximum static friction coefficient according to the GB / T 10006-2021 standard, and the comparison was repeated every month. The performance is shown in Table 4.
[0082] Table 4
[0083]
[0084]
[0085] It can be seen from the test results of Application Examples 1 to 3 and the comparative example that the POE film of the present invention uses a homemade graftable polycyclic material, which can significantly reduce the changes in the film during use, and the film containing a polymer grafted material such as Application Example 3 has a slower trend in the change of the friction coefficient, which proves that the grafted color conversion film has a more stable morphology, thereby obtaining a longer service life of the film.
[0086] Those skilled in the art should understand that those skilled in the art can implement variations by combining the prior art and the above embodiments, which will not be described in detail here. Such variations do not affect the essential content of the present invention, and will not be described in detail here.
[0087] The above describes the preferred embodiments of the present invention. It should be understood that the present invention is not limited to the above-mentioned specific embodiments, and the devices and structures that are not described in detail should be understood to be implemented in a common manner in the art; any technician familiar with the art can use the above-disclosed methods and technical contents to make many possible changes and modifications to the technical solutions of the present invention without departing from the scope of the technical solutions of the present invention, or modify them into equivalent embodiments of equivalent changes, which does not affect the essential content of the present invention. Therefore, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solutions of the present invention are still within the scope of protection of the technical solutions of the present invention.
Claims
1. A graftable condensed ring material, characterized in that: Including compounds having the structure shown in (I) or (II): Wherein, R1 and R2 are selected from H, substituted or unsubstituted alkyl, substituted or unsubstituted alkenyl, substituted or unsubstituted heteroalkyl, substituted or unsubstituted aryl, substituted or unsubstituted heteroaryl, substituted or unsubstituted amino, substituted or unsubstituted amide, substituted or unsubstituted cycloimido, substituted or unsubstituted alkoxy, substituted or unsubstituted carboxyl, substituted or unsubstituted ester, substituted or unsubstituted carbonyl, and R1 and R2 are not H at the same time; the substituted substituents include C1~C 20 Hydroxyl, C1~C 20 Ester group, C1~C 20 Carboxyl, C1~C 20 Amino, C1~C 20 Thiol, C1~C 20 Amide group, C1~C 20 Carbonyl, C1~C 20 Alkoxy, C1~C 20 Aryl, C4~C 20 Heteroaryl, C1~C 20 Alkyl, C1~C 20 Heteroalkyl, C1~C 20 Alkenyl and C1~C 20 Any of the imino groups; The L is taken from C1~C 20 Alkylene, C1~C 20 Ether group, C1~C 20 Ester group, C1~C 20 Imino, C1~C 20 Imido, C1~C 20 Carbonyl, C1~C 20 Arylene, C1~C 20 Alkenylene, C1~C 20 Any of alkynylene; The Ar1, Ar2 and Ar3 are independently selected from null, substituted alkylene, optionally substituted alkenylene, optionally substituted arylene, optionally substituted heteroarylene, ketone, ester and m=0-10000, Ar is an optionally substituted aryl or an optionally substituted heteroaryl; R3 is selected from H, alkyl, alkenyl, aryl, heteroaryl, aralkyl and alkaryl; n=1~10000; x+y=1.
2. A graftable fused ring material according to claim 1, characterized in that: The substituents in the optionally substituted aryl and optionally substituted heteroaryl are each independently one or more groups selected from the following groups: C1-C 20 Alkyl, C1-C 20 Alkenyl, C1-C 20 Alkynyl, C3-C7 cycloalkyl, geminal cycloalkyl, C1-C 20 Heteroalkyl, C3-C 200 heterocycloalkyl, aryl, aralkyl, heteroaryl, halo, cyano, hydroxy, optionally substituted cyclic imido, amino, imido, acylamino, C1-C 20 Alkoxy, aryloxy, acyloxy, mercapto, halogenated (C1-C 20 ) alkyl, C1-C 20 Alkylthio, arylthio, mono- and di-(C1-C 20 ) alkylamino, quaternary ammonium salt, amino (C1-C 20 ) alkoxy, hydroxyl (C1-C 20 ) alkylamino, amino (C1-C 20 ) alkylthio, cyanoamino, nitro, carbamoyl, oxy, carbonyl, carboxyl, glycolyl, glycyl, hydrazine, amidino, sulfonamide, sulfonyl, sulfinyl, thiocarbonyl, thiocarboxyl, sulfonamide, ester, C-amide, N-amide, N-carbamate, O-carbamate, urea, and combinations thereof.
3. The graftable fused ring material according to claim 1, characterized in that: The R1 and R2 are each independently selected from H, substituted or unsubstituted C1-C 20 Alkyl, substituted or unsubstituted C1~C 20 Any of alkenyl.
4. The graftable fused ring material according to claim 1, characterized in that: The graftable fused ring material includes any one or a combination of at least two of the following compounds:
5. A color light conversion film, characterized in that: The raw materials for preparing the color light conversion adhesive film include the graftable condensed ring material as described in any one of claims 1 to 4.
6. The color conversion adhesive film according to claim 5, characterized in that: The preparation raw materials also include the following components: resin, crosslinking agent, modified silane, acrylate, light stabilizer and anti-stabilizer.
7. The color conversion adhesive film according to claim 6, characterized in that: The raw materials for preparation include the following components in parts by weight:
8. The color conversion adhesive film according to claim 6, characterized in that: The resin includes any one or a combination of at least two of polyvinyl acetate, polyethylene-octene copolymer, polyvinyl butyral, hot-melt polyolefin particles or thermoplastic polyurethane; The cross-linking agent includes any one of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, triallyl isocyanurate, triallyl cyanurate, diisopropylbenzene peroxide, benzoyl peroxide, di-tert-butyl peroxide or diisopropylbenzene hydroperoxide, or a combination of at least two thereof; The modified silane includes any one or a combination of at least two of isocyanatepropyl trioxyethyl silane, vinyl triacetoxy silane, methacryloxypropyl trimethoxy silane derivatives, alkylamino silane oligomers, alkylvinyl silane oligomers, epoxy silane oligomers, amino silane oligomers, small molecule polysiloxanes, mercapto silane derivatives or hybrid functional silanes; The acrylate includes any one of ethoxylated trimethylolpropane triacrylate, propoxylated trimethylol triacrylate, trimethylolpropane triacrylate, pentaerythritol tetraacrylate, polyethylene glycol diacrylate, tricyclohexane dimethanol diacrylate or ditrimethylolpropane tetraacrylate, or a combination of at least two thereof; The light stabilizer includes any one of succinic acid, a polymer of 4-hydroxy-2,2,6,6-tetramethyl-1-piperidinol, bis-2,2,6,6-tetramethylpiperidinol sebacate or a hindered amine light stabilizer, 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene, tris(2,4-di-tert-butylphenyl) phosphite or 2,2,6,6-tetramethyl-4-piperidinyl ester or a combination of at least two thereof; The antioxidant includes any one of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate or tris[2,4-di-tert-butylphenyl]phosphite or a combination of at least two thereof.
9. A photovoltaic module, characterized in that The photovoltaic module comprises the color conversion adhesive film and a battery as described in any one of claims 5 to 8.
10. The photovoltaic module according to claim 9, characterized in that: The cell includes any one or a combination of at least two of an indium gallium arsenide solar cell, an organic solar cell, a perovskite solar cell, a cadmium sulfide / cadmium telluride solar cell, an amorphous silicon solar cell, a microcrystalline silicon solar cell, and a crystalline silicon solar cell.